Mini-open anterior approach to the cervicothoracic junction: a cadaveric study - Huang, Yi-xing (Springer Berlin Heidelberg, 2013)
PURPOSE: To investigate the feasibility of mini-open anterior approach to the cervicothoracic junction (CTJ) in cadaveric specimens. METHODS: Four adult fresh-frozen cadaveric specimens were used for this study. On the cadaveric specimen, an osteotomy window was made in manubrium sterni to remove the bony obstacle. To bypass the vital vascular and neural structures over the operative field, we used the surgical corridor which was located medially by the brachiocephalic artery and laterally by the right brachiocephalic vein, or in combination with another surgical corridor between the ascending aorta and the superior vena cava. And we used a special self-retaining retractor system and an endoscope to facilitate the procedures. RESULTS: Surgical procedures performed on the four fresh-frozen cadaveric specimens to expose the CTJ through mini-open anterior approach were successful. The anterior surface of C6–T5 could be exposed, allowing complete decompression and application of locking plate and screws. The most caudal accessible vertebral body was T5 vertebral body in our study. CONCLUSION: It is feasible to expose the CTJ through this mini-open anterior approach.